2010
DOI: 10.1177/1049909110365072
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Older Patients With Cancer in Phase 1 Clinical Trials: A Qualitative Case Series

Abstract: This article explores the experiences of older patients with cancer in phase 1 clinical trials. Conducting a case series of face-to-face, in-depth, open-ended interviews and using qualitative methods of analysis, we find that the psychosocial process of social comparison is relevant for understanding older adults' phase 1 clinical trial participation. Social comparison influences decisions to enroll in a phase 1 clinical trial, shapes perceptions of supportive care needs, and encourages the utilization of hope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…Wanting a cure. In general, wanting a cure was the primary motivation of patients to participate in a clinical trial (32,37,39,42). Several patients were willing to try anything that was suggested to them (40)(41)(42), and even though the treatment had proved ineffective on previous occasions, they were willing to try it again (38).…”
Section: Hope and Existential Mattersmentioning
confidence: 99%
“…Wanting a cure. In general, wanting a cure was the primary motivation of patients to participate in a clinical trial (32,37,39,42). Several patients were willing to try anything that was suggested to them (40)(41)(42), and even though the treatment had proved ineffective on previous occasions, they were willing to try it again (38).…”
Section: Hope and Existential Mattersmentioning
confidence: 99%
“…In 3 cross‐sectional studies and 1 qualitative study, most of the patients decided to participate independently of the influence of others; however, 1 qualitative study determined that the family's attitude was important . Comparing their own situation with that of others influenced the decision to participate in a qualitative study of older patients . Patients participating in a trial were less conflicted about the decision than those who rejected trial as described in a cross‐sectional study .…”
Section: Resultsmentioning
confidence: 99%
“…37 Comparing their own situation with that of others influenced the decision to participate in a qualitative study of older patients. 38 Patients participating in a trial were less conflicted about the decision than those who rejected trial as described in a cross-sectional study. 36 A cross-sectional study showed that poorer overall health was related to greater willingness to enter a phase 1 trial.…”
Section: Decision Makingmentioning
confidence: 94%
See 2 more Smart Citations